2023
DOI: 10.1002/path.6045
|View full text |Cite
|
Sign up to set email alerts
|

CDT1 drives replication overlicensing and enhances tumorigenesis in the gut

Abstract: Colorectal carcinoma (CRC) is one of the most common forms of malignancy in the Western world. Recent decades have witnessed enormous progress in our understanding of the mechanisms that sustain CRC, even though the factors implicated in the initiation and progression of this neoplasia are not fully understood. A recent study published in The Journal of Pathology looked at the consequences of hyperactivity of chromatin licensing and DNA replication factor 1 (CDT1), a regulator of DNA replication that is produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Our findings suggested down-regulation of genes associated with DNA replication in the jejunal mucosa of ODS patients, which may diminish intestinal regeneration and self-repair after damage. CDT1 , an essential component for the assembly of a pre-replicative complex[ 21 , 22 ], was down-regulated in these patients and network interaction analysis suggested that this gene plays a role in the development of ODS. A recent study reported an up-regulation of DNA replication licensing factors and robust acceleration of intestinal epithelial proliferation after glutamine (Gln) supplementation[ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings suggested down-regulation of genes associated with DNA replication in the jejunal mucosa of ODS patients, which may diminish intestinal regeneration and self-repair after damage. CDT1 , an essential component for the assembly of a pre-replicative complex[ 21 , 22 ], was down-regulated in these patients and network interaction analysis suggested that this gene plays a role in the development of ODS. A recent study reported an up-regulation of DNA replication licensing factors and robust acceleration of intestinal epithelial proliferation after glutamine (Gln) supplementation[ 23 ].…”
Section: Discussionmentioning
confidence: 99%